Foreign Investment and Non-Oil Export Development as Drivers of GCC Economic Diversification - Mili, Hela (Journal of Cultural Analysis and Social Change, 2025)
This study explores the ways in which the development of foreign direct investment and non-oil exports contributes to the overall economic diversification of the Gulf Cooperation Council's (GCC) countries between 2020 and 2025. A key aspect of long-term development as countries struggle with rising oil revenue volatility is the diversification of non-oil businesses. The growth of non-oil exports diversifies the economy away from hydrocarbons, and foreign direct investment (FDI) inflows are required for knowledge transfer, infrastructure modernization, and the integration of the region into global value chains. This study employs a dynamic panel data method using the Generalized Method of Moments (GMM) with annual data for all the six GCC countries: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates. This approach helps to better deal with potential endogeneity and to capture both the short- and long-run impacts. The key variables include FDI as a percentage of GDP, non-oil export quantities, and economic diversification measures, with controls for inflation, trade openness, and institutional quality. For building robust and diversified economies in the GCC nations, the empirical results show the significance of concerted policies that attract foreign investment while promoting non-oil sectors. They demonstrate that higher FDI has a significant impact on the performance of non-oil exports, which accelerates diversification.